2021
DOI: 10.1002/ddr.21884
|View full text |Cite
|
Sign up to set email alerts
|

IL2‐inducible T‐cell kinase inhibitor ibrutinib reduces symptoms and Th2 differentiation in mouse allergic‐rhinitis model

Abstract: Th2 and Th17 immune response contribute to allergic rhinitis (AR) development. Targeting Th2 and Th17 response has been shown to ameliorate AR. Ibrutinib is an inhibitor for IL2‐inducible T‐cell kinase, which can promote Th2 and Th17 immune response. We sought to investigate the effect of ibrutinib on AR and the underlying mechanisms. We established house dust mite‐induced AR mouse model and treated AR mice with ibrutinib. The symptoms of AR, serum level of immunoglobulin E, percentage of Th1, Th2, Th17, and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Studies had shown that the level of IL7R in sepsis was significantly reduced, which was consistent with our results [ 54 ]. ITK is a member of the Tec family tyrosine kinases and mediates T cell receptor (TCR) signaling pathway [ 55 ]. Nadeem A proposed that ITK signaling plays a significant role in sepsis-induced acute lung injury [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies had shown that the level of IL7R in sepsis was significantly reduced, which was consistent with our results [ 54 ]. ITK is a member of the Tec family tyrosine kinases and mediates T cell receptor (TCR) signaling pathway [ 55 ]. Nadeem A proposed that ITK signaling plays a significant role in sepsis-induced acute lung injury [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eight-week-old female BALB/c mice were provided via Charles River Laboratories (Beijing, China), and housed in a climate-controlled environment. The murine AR model was established as previously reported [24, 25]. In brief, 24 mice were randomly divided into 4 groups (control, AR, AR + pc-NC, or AR + pc-circARF3 group; n = 6 per group).…”
Section: Methodsmentioning
confidence: 99%
“…House dust mite (HDM) is a common allergen that has been utilized extensively to induce allergic inflammation in AR mice [24, 25]. Our study established an AR model using HDM-treated BALB/c mice and IL-4/IL-13-stimulated mice NEpCs.…”
Section: Introductionmentioning
confidence: 99%
“…qRT-PCR was performed as described previously. 18 Briefly, total RNA from cells was extracted using PureLink RNA Mini Kit (Thermo Fisher Scientific Corp.) and then reverse-transcribed to cDNA using a high-capacity cDNA reverse transcription kit (Thermo Fisher Scientific Corp.). Real-time PCR was performed with PowerUp SYBR Green Master Mix and performed using QuantStudio 5 Real-Time PCR System (Thermo Fisher Scientific Corp.).…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed following a standard protocol described previously. 18 Briefly, total proteins were extracted from cells by RIPA lysis buffer (Abcam, Cambridge, UK) and protein concentration was measured using a bicinchoninic acid (BCA) protein assay kit (Abcam). Equal amounts of protein (25 µg) resolved by SDS-PAGE and transferred to polyvinylidene difluoride (PVDF) membranes.…”
Section: Methodsmentioning
confidence: 99%